2003
DOI: 10.1002/humu.9167
|View full text |Cite
|
Sign up to set email alerts
|

The 342-kb deletion inGJB6is not present in patients with non-syndromic hearing loss from Austria

Abstract: Recently, a 342-kb deletion involving GJB6 was associated with autosomal-recessive nonsyndromic hearing loss (NSHL) and in combination with a GJB2 mutation with digenic NSHL. This deletion was the second most common mutation causing prelingual NSHL in Spain, and was frequently observed in patients from France and Israel. We screened 393 patients with NSHL being negative or heterozygous for GJB2 mutations for this GJB6 deletion using a multiplex PCR. Most patients were of Austrian (84.2%), and the other patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
11
17
0
Order By: Relevance
“…Our result is consistent with the results of Liu et al (2002), who did not detect this mutation in a sample from the Chinese population [37]. Since a number of other studies also found a low frequency or absence of this mutation in different populations, including Austrian, Russian, and Moroccan [23,[38][39][40][41], this deletion may be restricted to certain populations [23].…”
Section: Discussionsupporting
confidence: 92%
“…Our result is consistent with the results of Liu et al (2002), who did not detect this mutation in a sample from the Chinese population [37]. Since a number of other studies also found a low frequency or absence of this mutation in different populations, including Austrian, Russian, and Moroccan [23,[38][39][40][41], this deletion may be restricted to certain populations [23].…”
Section: Discussionsupporting
confidence: 92%
“…We did not detect any deletion among Iranian patients. Absence of this mutation among studied patients is similar to other studies from Iran and other countries (Gunther et al 2003;Kalay et al 2005;Esmaeili et al 2007). This result supports the view that del(GJB6-D13S1830) mutation is associated with only certain populations.…”
Section: Gjb2 Mutations and Deafness In Iransupporting
confidence: 90%
“…The frequency of the 342-kb deletion [Δ(GJB6-D13S1830)] affecting GJB6 varies tremendously between different populations. In our study, as well as in other studies of Polish and Austrian patients, the deletion was observed infrequently (36,37). In contrast, a multicenter study in nine countries revealed high mutation frequencies with the highest ones (32-72%) observed in France, Spain, Israel, and the UK (33).…”
Section: ------------------------------------------------------------supporting
confidence: 70%